DIFERENÇAS REGIONAIS E FATORES ASSOCIADOS AO RISCO DE NOVO EVENTO CARDIOVASCULAR EM INDIVÍDUOS EM PREVENÇÃO CARDIOVASCULAR SECUNDÁRIA: ESTUDO MULTICÊNTRICO. - TEIXEIRA, Adriana Fonseca (2018)
Introduction: Cardiovascular diseases along with their risk factors are a major global health problem. In Brazil, there are important regional differences related to cardiovascular morbidity and mortality in different regions of the country. Objective: To evaluate the regional differences and the factors associated with the risk of subsequent cardiovascular event in individuals in secondary cardiovascular prevention participating in the Brazilian Cardioprotective Food Program - DICA Br. Methods: Cross-sectional study of the randomized clinical trial - "Brazilian Cardioprotective Food Program Reduction of Events and Risk Factors in Secondary Prevention for Cardiovascular Disease: A Randomized Clinical Trial (DICA Br), "a multicenter study that included individuals who had evidence of established cardiovascular disease in the past 10 years. Socio-demographic, behavioral, clinical and nutritional variables were collected to analyze the risk of a new cardiovascular event, and the Framingham risk score (ERF) was used for a subsequent cardiovascular event. Categorical variables were presented as frequencies and compared using the Chi-square test. For the continuous variables, the Variance Analysis (ANOVA) test was applied for parametric variables and Kruskal Wallis for non-parametric variables. The Poisson multivariate regression model was used to identify the factors associated with the risk of subsequent cardiovascular event, with robust variance. The statistical analysis was performed by Stata® software (version 14,0). A significance level of 5% was adopted. Results: The highest percentage of illiteracy was identified in the northeast region (36,5%) (p <0,001). The highest percentage of persistent smokers in the southern region (13,6%). The highest frequency of physical inactivity in the central-west region (72,9%) and northeast (71,9%) (p <0,001). The South and Southeast regions had the highest rates of overweight among the elderly (61,2 and 52,3%, respectively), with a very high risk of developing cardiovascular disease evaluated by CC (66,2 and 60,5% , respectively) and high C index (94,4 and 95,4%, respectively). There was also a high percentage of dyslipidemia (89,2%), hypertension (94,8%), diabetes mellitus (50,8%) in the southeast region (p <0,001). In the adjusted analysis, the high risk of subsequent cardiovascular events remained significantly associated with age (≥ 60 years) (RP 1,58, 95% CI 1,39 – 1,78, p <0,001), female gender (RP 1, 95% confidence interval, 95% CI 1,29 to 1,64, p <0.001), diagnosis of diabetes mellitus (RR 1,45, 95% CI 1,30-1,60, p <0,001), high systolic blood pressure ) (RP 1,31, IC 95% 1,17 – 1,46, p <0,001), elevated triglycerides (≥ 150 mg / dL) (PR 1,56, 95% CI 1,38) – 1,77, p <0,001) and elevated LDL-cholesterol (≥ 100 mg / dL) (PR 3,20, 95% CI 2,83-3,63, p <0,001). Conclusions: regional differences were striking. The risk of subsequent cardiovascular event was associated with gender, age, diagnosis of diabetes mellitus, and elevated serum triglyceride and LDL-c levels.